Sosialisasi Penularan Penyakit Covid-19 Pada Lansia Di Posyandu Lansia Puskesmas Harapan Distrik Sentani - Sulistiyani Sulistiyani; Lamria Situmeang; I Ketut Swastika (Poltekkes Kemenkes Jayapura, 2021)
Abstract Elderly people are a vulnerable group who are susceptible to infectious diseases. During the pandemic, the death rate of the elderly because of the disease Covid-19 with a degenerative disease. The center for Disease Control and Prevention (CDC) said that the population aged 65 years or as many as 17% of the total population in the United States has been exposed to the infection of Covid-19 as much as 80% of deaths. Attempts to do so is not infected with coronavirus is to enhance knowledge through training behavior of the healthy and clean living (PHBS) in the elderly.service Activities using the training methods, lectures, simulations/role-play to the elderly. The Media used booklets and interactive videos as well as the questionnaire of the level of knowledge and attitude of the elderly about the disease Covid-19. Assessment of the level of knowledge of the elderly conducted by the method pre-post intervention.The Results of community service activities include a pre-test, the socialization of the disease covid-19 and ways of prevention, the simulation of how the prevention of Covid-19, the socialization of elderly health care, and evaluation activities. The results of testing the knowledge before training the good category as many as 70% and 30%. As for the level of knowledge after the training the good category as many as 90% and 10%.Prevention of the spread of the disease Covid-19 can be overcome with the provision of the information periodically. Spread information quickly and gives the effect of reducing the transmission of infection of Covid-19 in the elderly such as the activities of PHBS, social distancing, and screening health regularly. The provision of training with the system role-play and video media is considered effective in the efforts to empower the elderly. The elderly as a vulnerable group is more receptive to the information in a visual form. That is because in the elderly there are already declining or aging processes that also have an impact on the cognitive elderly. Abstrak Lansia merupakan kelompok rentan yang mudah terkena penyakit infeksius. Pada masa pandemi, angka kematian lansia karena penyakit Covid-19 dengan penyakit degenerative. Pusat Pengendalian dan PencegahanPenyakit (CDC) mengatakan bahwa penduduk yang berusia 65 tahun atau sebanyak 17% dari total populasi di Amerika Serikat telah terpapar infeksi Covid-19 sebanyak 80% kematian. Upaya yang dapat dilakukan agar tidak terinfeksi virus corona adalah dengan meningkatkan pengetahuan melalui pelatihan perilaku hidup sehat dan bersih (PHBS) pada lansia. Kegiatan pengabdian menggunakan metode pelatihan, ceramah, simulasi/role play kepada para lansia. Media yang digunakan booklet dan video interaktif serta kuisioner tingkat pengetahuan dan sikap lansia tentang penyakit Covid-19. Penilaian terhadap tingkat pengetahuan lansia dilakukan dengan metode pre-post intervensi. Hasil kegiatan pengabdian kepada masyarakat meliputi pre-test, sosialisasi penyakit covid-19 dan cara pencegahan, simulasi cara pencegahan Covid-19, sosialisasi posyandu lansia, dan evaluasi kegiatan. Hasil pengujian gambaran pengetahuan sebelum pelatihan kategori baik sebanyak 70% dan cukup 30%. Sedangkan untuk tingkat pengetahuan setelah pelatihan kategori baik sebanyak 90% dan cukup 10%. Pencegahan peyebaran penyakit Covid-19 dapat diatasi dengan adanya pemberian informasi secara berkala. Penyebaran informasi yang cepat dan tepat dapat memberikan efek mengurangi transmisi penularan infeksi Covid-19 pada lansia seperti kegiatan PHBS, social distancing, dan screening kesehatan secara rutin. Pemberian pelatihan dengan sistim role play dan media video dinilai efektif dalam upaya memberdayakan lansia. Lansia sebagai kelompok rentan lebih mudah menerima informasi dalam bentuk visual. Hal tersebut dikarenakan pada lansia sudah ada kemunduran atau aging process yang juga berdampak pada kognitiflansia.